Phase-Dependent Color Polyphenism in Field Populations of Red Locust Nymphs (Nomadacris septemfasciata Serv.) in Madagascar - Michel Lecoq; Abdou Chamouine; My-Hanh Luong-Skovmand (Psyche: A Journal of Entomology)
Pigmentation of the Red locust hopper, Nomadacris septemfasciata Serv., was studied in natural conditions in Madagascar in relation to population density. More than one thousand hoppers were collected and described according to a semiquantitative method. A typology is proposed, strictly reflecting the increase in population densities. This correctly translated the progressive evolution of a solitary state into a gregarious state, while passing through several intermediate transiens stages. According to their density, hopper populations consist of a mixture, in various proportions, of several pigment types. The gregarization threshold is estimated at 100,000 hoppers/ha. A slight black spot on the hind femur is the first sign of gregarization. These results should improve the reliability of the information collected by the Malagasy National locust centre when surveying this major pest. They question the rapidity of the gregarization process in natural conditions as well as the stimuli involved.